Men in relationships : a new look from a life course perspective - Bedford, Victoria Hilkevitch; Turner, Barbara F. (Springer series, focus on men (Unnumbered), 2006)
Annotation "From relationships men have with their wives to relationships men have with their brothers and friends, this dynamic presentation offers a unique perspective and explores diverse points of life with a focus on middle to old age. Engaging commentary provides useful overviews of traditional and current topics."--Jacket